Buprenorphine 5, 10 and 20?gh transdermal patch: A review of its use in the management of chronic non-malignant pain (2011)
This article reviews the pharmacology, therapeutic efficacy and tolerability profile of the 7-day lower-dose (5, 10 and 20?gh) buprenorphine transdermal patch (BuTrans®, Norspan®) in the management of chronic non-malignant pain, with a focus on European labelling for the drug. Buprenorphine is a semi-synthetic opioid analgesic that acts primarily as a partial agonist at the mu opioid receptor. The transdermal formulation provides continuous delivery of buprenorphine, resulting in relatively consistent plasma drug concentrations throughout the 7-day dosing interval.The analgesic efficacy of transdermal buprenorphine in patients with osteoarthritis of the hip andor knee has been demonstrated in several randomized controlled trials, which have shown the formulation to be equivalent to sublingual buprenorphine, noninferior to prolonged-release tramadol tablets, noninferior to codeine plus paracetamol (acetaminophen) combination tablets (when transdermal buprenorphine was used together with regularly scheduled oral paracetamol) and generally superior to a matching transdermal placebo patch. Transdermal buprenorphine was significantly more effective than placebo in reducing chronic low back pain of at least moderate severity in two randomized, double-blind, crossover trials. Other clinical trials, including a randomized, double-blind, maintenance-of-analgesia study, have also demonstrated the analgesic efficacy of transdermal buprenorphine in patients with chronic non-malignant pain of various causes.In general, serious adverse events with transdermal buprenorphine are similar to those for other opioid analgesics. Transdermal buprenorphine has a ceiling effect for respiratory depression, and the main risk is when it is combined with other CNS depressants. The most frequently reported adverse events with transdermal buprenorphine are headache, dizziness, somnolence, constipation, dry mouth, nausea, vomiting, pruritus, erythema, application site pruritus and application site reactions. Transdermal buprenorphine was better tolerated than sublingual buprenorphine in a 7-week, randomized, double-blind trial in patients with osteoarthritis pain. Nevertheless, as with other opioids, persistence with transdermal buprenorphine therapy is difficult for many patients because of adverse events or other reasons.Thus, transdermal buprenorphine has generally demonstrated good efficacy and tolerability in clinical trials in chronic non-malignant pain, providing effective background analgesia as part of pain management strategies for patients with osteoarthritis, low back pain and other persistent pain syndromes of at least moderate severity. It also has favourable pharmacodynamic and pharmacokinetic properties, which have beneficial clinical implications, most notably the convenience of once-weekly administration and no need for dosage adjustments in the elderly or those with compromised renal function, making it an opioid of choice in these patients, and a useful therapeutic option overall in the management of chronic non-malignant pain. © 2011 Adis Data Information BV. All rights reserved.